Hands-on start to WolframAlpha notebook edition - Hastings, Cliff; Mischo, Kelvin (Wolfram Media, Inc., 2020)
Wolfram|Alpha Notebook Edition combines the simplicity of Wolfram|Alpha® with the computational capabilities of Mathematica® for the best of both in a single, unified tool perfect for teaching and learning. Use free-form input to get instant answers to questions, create and customize graphs, and turn static examples into dynamic models. Everything is saved as an interactive Wolfram Notebook, so you can add notes and use notebooks as class or reference materials, or present them as dynamic slide shows that engage your audience as you edit examples on the fly. With this book, you'll learn how to... -Quickly create notebooks that combine calculations, graphics, interactive examples and notes. -Enter free-form input and get solutions for a variety of calculations (e.g. arithmetic, algebra, calculus, linear algebra). -Access step-by-step solutions, suggestions for next steps and related computations. -Create 2D, 3D and interactive graphics with controls to dynamically change the parameters. -Use previous results in future calculations, assign variables and define functions. -Create dynamic slide show presentations with interactive elements that can be changed on the fly"--